The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0244655
|View full text |Cite
|
Sign up to set email alerts
|

Personality and the use of cancer screenings. A systematic review

Abstract: Background No systematic review exists synthesizing studies examining the association between personality factors and use of cancer screenings. Hence, the aim of this systematic review is to provide an overview of empirical findings from observational studies investigating the link between personality factors (in terms of agreeableness, conscientiousness, extraversion, neuroticism and openness to experience) and use of cancer screenings. Methods Medline, PsycInfo and CINAHL were searched using predefined sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…Usually they are more task and goal-directed and the association to longtime regular dental visits appears plausible. A systematic review reported an association between extraversion and conscientiousness with increased uptake of cancer screening [ 23 ]. This is in line with our findings and it is suspected, that individuals with higher scores in extraversion are in general more sociable and energetic, thus having a more positive attitude towards their dental appointments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually they are more task and goal-directed and the association to longtime regular dental visits appears plausible. A systematic review reported an association between extraversion and conscientiousness with increased uptake of cancer screening [ 23 ]. This is in line with our findings and it is suspected, that individuals with higher scores in extraversion are in general more sociable and energetic, thus having a more positive attitude towards their dental appointments.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies suggested that personality traits might be related to treatment adherence and compliance [ 25 , 26 ], treatment medication adherence [ 27 , 28 ], and doctor visits in general [ 29 , 30 ], which in certain conditions significantly reduce quality of life [ 29 ], such as in rheumatoid arthritis [ 31 , 32 ], depression [ 33 , 34 ], attention deficit hyperactivity disorder [ 35 ], multiple sclerosis [ 36 ], and cancer screening [ 23 ]. Oral diseases are also a significant contributor to reduced quality of life [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neuroticism seems to predispose various unhealthy behaviors such as eating unhealthily (Booth-Kewley & Vickers, 1994;Sirois & Hirsch, 2015). However, because neurotic individuals are also concerned about their health (Van Dijk et al, 2016), they show increased healthcare utilization (for a review see Hajek et al, 2020). Additionally, neuroticism is positively related to getting vaccinated against influenza (Brewer & Hallman, 2006;Nolan et al, 2019) and to positive attitudes towards vaccinations in general (Lin & Wang, 2020; but see Demir et al, 2020 for null effects).…”
Section: Big Five and Health Behaviormentioning
confidence: 99%
“…The correlations between malignancy and psychological factors such as personality traits, stress, depression, social isolation, and emotional reactions have been investigated for years by both researchers and practitioners. However, despite all efforts, the topic remains to be fully elucidated [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%